Effectiveness of Generation of Red Ginger and Mint Leaves to Reduce Hyperemisis Gravidarum in the 1st Trimester Pregnant Women - Eka Rahayuningsih; Tuty Yanuarti (STIKep PPNI Jawa Barat, 2023)
Aims: The incidence of emesis gravidarum is 14 % of all expectant women worldwide. In five European, American, and Australian jurisdictions, approximately 73.5 percent of pregnant women experience emesis. Up to 75 % of expectant women in Indonesia experience nausea and vomiting in the first trimester or early pregnancy. Several pharmacological and non-pharmacological actions can contribute to efforts to reduce the frequency of regurgitation. Non-pharmacologically, herbal plants, such as red ginger and peppermint leaves, are readily available. Methods : One-group, quasi-experimental, pretest-posttest design. This study's sample consisted of all 35 expectant women in the first trimester of PMB